The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Proceedings of the Tenth ACM SIGKDD International Conference on Knowledge Discovery and Data Mining 2004
DOI: 10.1145/1014052.1014098
|View full text |Cite
|
Sign up to set email alerts
|

Predicting customer shopping lists from point-of-sale purchase data

Abstract: This paper describes a prototype that predicts the shopping lists for customers in a retail store. The shopping list prediction is one aspect of a larger system we have developed for retailers to provide individual and personalized interactions with customers as they navigate through the retail store. Instead of using traditional personalization approaches, such as clustering or segmentation, we learn separate classifiers for each customer from historical transactional data. This allows us to make very fine-gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 16 publications
0
36
0
1
Order By: Relevance
“…State-of-the-art methods [5,21,26,29] must fix the size of the predicted basket. Here choices of n = 5 or n = 10 are common; however, we found that this impedes the performance given the large assortment in our experiments.…”
Section: A3 Estimation Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…State-of-the-art methods [5,21,26,29] must fix the size of the predicted basket. Here choices of n = 5 or n = 10 are common; however, we found that this impedes the performance given the large assortment in our experiments.…”
Section: A3 Estimation Detailsmentioning
confidence: 99%
“…. , 30,35] Number of k -nearest neighbors [1,2,5,10,20] Table 6: Hyperparameters with tuning ranges. Note that the small number of hyperparameters contributes to the robustness of our approach, as well as our evaluation.…”
Section: Parametermentioning
confidence: 99%
“…To solve this problem in the literature various methods have been adopted: collaborative filtering [20], Markov chains [21], supervised classification algorithms [22], deep neural networks [23], and temporal frequent pattern mining algorithms [24]. However, all these methods only exploit the temporal dimension but do not provide a way to understand how the time affects the customers decisions and which are the typical temporal shopping patterns.…”
Section: Related Workmentioning
confidence: 99%
“…A popular task has been to generate personalized product recommendations based on customer transaction data. For example, Cumby et al [2004] predict customers' shopping lists using individualized classifiers that are trained using their recent transaction histories. The predictions are used to remind customers of forgotten products and to target promotions.…”
Section: Related Researchmentioning
confidence: 99%